Analysis of procurement of selected agricultural products in Poland in the years 2010-2016 - Elżbieta Roszko-Wójtowicz; Maria M. Grzelak (Economic and Environmental Studies (E&ES), 2018)
Economic development is characterised by the fact that the share of agriculture tends to decrease both in terms of resources used and domestic product generated. This does not mean, however, that the role of agriculture in the economic development diminishes. It can be considered a paradox that the lower the share of agriculture in the national economy, the greater its role, as it provides raw materials for the production of goods, especially food, which meet the needs of the ever-growing community. The main aim of the presented study is to measure and evaluate changes in agricultural produce procurement in Poland in the years 2010-2016. The following research hypothesis is put forward in the study: Changes in the procurement volume had a much greater impact on the procurement value of selected agricultural produce in Poland in the period considered than changes in the level of transaction prices. In the paper, a comparative analysis of procurement of crop and animal products was conducted. The research process was based primarily on data derived from official statistics obtained from the Central Statistical Office and the Eurostat database regarding procurement of agricultural produce carried out by commercial entities and processing plants. This information is presented in qualitative and quantitative terms for total agriculture, as well as for individual voivodeships.
Keywords: Q10; C20; 330; agriculture; procurement of agricultural produce; crop production; animal production; dynamics analysis; aggregate indices